How capitalism was built : the transformation of Central and Eastern Europe, Russia, and Central Asia - Åslund, Anders, 1952- (Cambridge : Cambridge University Press, 2007)
Anders Åslund foresaw the collapse of the Soviet Union in his book Gorbachev's Struggle for Economic Reform (1989). He depicted the success of Russia's market transformation in How Russia Became a Market Economy (1995). After Russia's financial crisis of 1998, Åslund insisted that Russia had no choice but to adjust to the world market (Building Capitalism, 2001), though most observers declared the market economic experiment a failure. Why did Russia not choose Chinese gradual reforms? Why are the former Soviet countries growing much faster than the Central European economies? How did the oligarchs arise? Who is in charge now? These are just some of the questions answered in How Capitalism Was Built, covering twenty-one former communist countries from 1989 to 2006. Anybody who wants to understand the confusing dramas unfolding in the region and to obtain an early insight into the future will find this book useful and intellectually stimulating.
Communism and its demise. Real socialism. Decline and fall of socialism. The demise of communism in Central Europe. The collapse of the Soviet Union -- Shock therapy vs. gradualism. The radical reform program : a big bang. Gradual reform programs. Rent seeking : the scourge of transition. Criticism of radical reform after the Russian financial crash -- Output : slump and recovery. Sharp decline in recorded output and varied recovery. Exaggeration of the slump. Radical reform : least decline and early recovery. Late reformers : surged after 1998 -- Liberalization : the creation of a market economy. Different strategies of deregulation. Liberalization of foreign trade. Labor market policy. Combat of monopoly : gas and coal. A big bang : vital in deregulation -- From hyperinflation to financial stability. Establishing national currencies. Radical fiscal adjustment was key. Tax policy : from social democratic to liberal. Monetary policy : from loose to strict. Exchange rates : currency board or free float. Dramas of financial stabilization -- Privatization : the establishment of private property rights. Differing aims of privatization. Small-scale privatization : if started, swiftly done. Large-scale privatization : the biggest headache. Privatization of land, real estate, and housing. New enterprise development : the ultimate success. Great achievements of privatization. Vital : speed and legitimacy of property rights -- An inefficient social system. Incomes : differentiation and poverty. Life and health. Education adjusting to demand. Social transfers and pension reform. Alternative social models -- Democracy vs authoritarianism. Democratic breakthrough : critical for successful transformation. An under-reform trap. Renewed democratization : colored revolutions. Parties, electoral rules, and constitutions. How to tame the leviathan : reform of the communist state. Public opinion and ideology. Democracy and democracy aid -- From crime toward law. An explosion of cr
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: elektronické knihy; electronic books; Post-communism -- Former communist countries; Privatization -- Former communist countries; Former communist countries -- Economic policy; Former communist countries -- Economic conditions